Application of reliability-centered maintenance in a steel mill - Bastos, Filipe Carneiro; Fujiyama, Roberto Tetsuo (Brazilian Journal of Production Engineering, 2023)
The technological development has been causing several changes in the industrial process and has led to the need for maintenance improvement due to the importance of operational availability for companies' results. In this study, the goal was to apply Reliability Centered Maintenance (RCM) to the highly critical equipment of a steel mill's blast furnace and to present the benefits obtained after implementation. As an initial sample, the motor starters in the engine room were used, given the high number of corrective maintenance actions and long downtimes during failure occurrences. For the method's applicability, the five implementation stages were followed, and finally, a comparison was made between the maintenance plans before and after RCMRCM implementation, presenting the gains achieved through a reduction in the number of corrective maintenance actions in a specific analysis period. By applying RCMRCM to the equipment with criticality A, there was a decrease in corrective maintenance actions in 2022 compared to 2021, as well as an increase in MTBF (Mean Time Between Failures) and a reduction in MTTR (Mean Time to Repair) for the studied equipment.
Keywords: Reliability-Centered Maintenance; Blast Furnace; Steel Mill